PENGARUH MUTU PEMBELAJARAN ONLINE DAN TINGKAT KEPUASAN MAHASISWA TERHADAP HASIL BELAJAR SAAT PANDEMI COVID19 - Prasetya, Tri Adi; Harjanto, Chrisna Tri (Jurnal Pendidikan Teknologi dan Kejuruan, 2020)
The application of physical distancing policies to reduce the spread of the covid19 virus changed learning activities from face-to-face models to online learning models. Online lectures, even if they are held online, must pay attention to the quality of learning so that learning outcomes are met. This research was conducted to find out (1) the effect of online learning quality on learning outcomes, (2) the effect of student satisfaction levels on learning outcomes, (3) the effect of online learning quality and student satisfaction levels on learning outcomes during pandemic covid19. The respondents of this study were 34 Vocational Learning Media students. Data collection using questionnaires and documentation methods. The data analysis technique used is a simple regression analysis technique for the first and second hypotheses and multiple regression analysis for the third hypothesis. The results showed there was an influence of the quality of online learning on learning outcomes with t arithmetic higher than the t table (3.024> 1.65) or p (0.01 <0.05). The student satisfaction level has a significant influence on learning outcomes with t arithmetic higher than the t table (2.571> 1.65) or p (0.01 <0.05). Based on the results of the analysis showed that the coefficient of determination X1 and X2 to Y amounted to 0.155. The results of the analysis show that the variables of the Online Learning Quality and Satisfaction Level have a contributing effect on Learning Outcomes.